Effects of social support and grateful disposition on employees' psychological well-being. Issue 11 (10th September 2019) - Cho, Sanglee
ABSTRACT: This study proposes grateful disposition as an individual affective factor affecting service employees' psychological well-being. Grateful disposition is the tendency to recognize and appreciate the contributions of others as positive experiences or to experience gratitude easily. To analyze the relationship between emotional dissonance and psychological well-being and the moderating effect of social support and grateful disposition, hierarchical regression analysis was used. Using convenience sampling from department store employees ( n = 239) in Korea, this study found that grateful disposition as well as social support moderated the relationship between emotional dissonance and psychological well-being. This study demonstrates the importance of individual affective traits affecting psychological well-being, which were overlooked in the previous studies, and provides an opportunity to discuss grateful disposition in service marketing.